School Administration With National Standards of Education to Improve the Quality of Education Indonesia - Helda Daniati (Indonesian Journal of Education (INJOE), 2022)
School administration is the entire management process, starting from controlling, managing and regulating various ways or efforts so that school goals can be implemented. Management of the development of Graduate Competency Standards and Educators and Education Personnel Standards is a program to determine the quality of education. To encourage the improvement of the quality of education in Indonesia, the government implements a standardization of the education system that must be applied by all educational institutions in Indonesia. The program was called the National Education Standards which later became the basis for the government to plan, implement, and supervise education. By implementing this standardization, it is hoped that there will be an increase in the quality of education in Indonesia. In its preparation, the National Education Standards have been perfected with full planning, direction and sustainability, adjusting for life changes that occur on a national and global scale